2016
DOI: 10.1097/ccm.0000000000001371
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Pressure Variation Adjusted by Respiratory Changes in Pleural Pressure, Rather Than by Tidal Volume, Reliably Predicts Fluid Responsiveness in Patients With Acute Respiratory Distress Syndrome*

Abstract: In acute respiratory distress syndrome patients, pulse pressure variation adjusted by changes in pleural pressure is a reliable fluid responsiveness predictor despite the low tidal volume (< 8 mL/kg). The poor predictive ability of pulse pressure variation in acute respiratory distress syndrome patients is more related to low chest wall elastance/respiratory system elastance ratios than to a low tidal volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Although an absence of spontaneous breathing was confirmed clinically by observing the capnograph waveform, variations in PIP, and the animal's chest movements, it is possible that small respiratory efforts affected values of PPV and PVI because a neuromuscular blocking agent was not used. Second, the measurement of PPV and PVI can be directly affected by a change in TV, PIP, and a pleural pressure . In this study, the relatively high VT of 15 mL/kg was set in order to avoid a low VT that may produce unreliable PPV, but the current study's setting resulted in clinically acceptable PIP and P ETCO2 (Table ).…”
Section: Discussionmentioning
confidence: 96%
“…Although an absence of spontaneous breathing was confirmed clinically by observing the capnograph waveform, variations in PIP, and the animal's chest movements, it is possible that small respiratory efforts affected values of PPV and PVI because a neuromuscular blocking agent was not used. Second, the measurement of PPV and PVI can be directly affected by a change in TV, PIP, and a pleural pressure . In this study, the relatively high VT of 15 mL/kg was set in order to avoid a low VT that may produce unreliable PPV, but the current study's setting resulted in clinically acceptable PIP and P ETCO2 (Table ).…”
Section: Discussionmentioning
confidence: 96%
“…This finding is not unexpected since cardiopulmonary interactions under mechanical ventilation (the underlying physiological mechanism behind PPV) are dependent on both ventilatory settings and transmission of airway pressure to cardiac filling pressures. This transmission is inversely related to respiratory system elastance [ 15 ], and linearly related to the ratio of chest wall to respiratory system elastances [ 36 ]. In conditions combining low VT and low respiratory system elastance as observed in patients with ARDS under protective ventilation, a high rate of false negative patients is expected.…”
Section: Discussionmentioning
confidence: 99%
“…De Baker and Scolletta [38] demonstrated that low tidal volume (<8 ml/kg) invalidates the cutoff value of 12 % for pulsed pressure variation (PPV) (a surrogate of stroke volume variation). In an attempt to solve this problem, Liu et al [39] suggested estimating pleural pressure variations as a surrogate of thoracic pressure variations in ARDS patients and then adjusting the PPV accordingly in order to improve prediction and prevent false negatives for fluid responsiveness. This approach, however, requires measurement of esophageal pressure using a balloon catheter, increasing the complexity of care, and is therefore used clinically in a small number of centers.…”
Section: Clinical Methods At the Bedside To Assess Volume Responsementioning
confidence: 99%